Comparative assessment of the sensitivity of oilseed rape and wheat to limited water supply. (9th April 2015) - Hess, Linde; Meir, Patrick; Bingham, Ian J.
Abstract The drought‐sensitivity of oilseed rape (OSR, Brassica napus cv. SW Landmark) was investigated, using the more widely studied crop species wheat (Triticum aestivum cv. Tybalt) as a benchmark. The water relations of OSR and wheat were compared in lysimeter and controlled environment experiments to test the hypothesis that the growth of OSR is restricted to a greater extent by soil drying than wheat and to determine whether the greater sensitivity results from differences in root or shoot traits. Plants were grown, with or without irrigation, in 1.2 m tall lysimeters packed with a sandy clay loam soil. The experiment was conducted in an open‐sided glasshouse to encourage air flow and to resemble a field environment as far as possible; plant population densities were equivalent to commercial crops. Irrigated OSR (evapo)transpired more water than wheat (498 vs. 355 mm), but had a comparable water use efficiency (WUE; 4.1 vs. 4.4 g DW mm−1 H2O). Oilseed rape showed a greater reduction in above‐ground growth (52% vs. 21%) and a smaller increase in WUE (27% vs. 45%) when water was withheld. Oilseed rape also responded to soil drying at a lower soil moisture deficit than wheat; transpiration rates fell below the potential of irrigated plants when plant available water remaining in the soil profile declined from 54 to 23% compared to 38 to 9% for wheat. The root hydraulic conductivity of young OSR plants, measured on root surface area basis, was about twice that of wheat, and was comparable on a root length basis. The results show that OSR was more sensitive to a restricted water supply than the benchmark species wheat and that the greater sensitivity resulted from differences in shoot, rather than root, characteristics. The root system of OSR was at least as efficient as wheat at extracting water from soil.